Perkembangan industri kreatif di kota Batu, Jawa Timur 2001-2022 - Pradani, Ersa Aprilia (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The creative industry is an economic sector powered by individual creativity, talent, and skills, which generates both additional value and employment opportunities. In Batu City, its growth is parallel to urban development while structural barriers still exist. As such, the study analyzes the city’s creative industry development from 2001 to 2022 using a historical approach involving source collection, critique, interpretation, and historiography. It was inspired by Ibn Khaldun’s integration of economic and sociological analysis. The findings indicate an increase in the number of creative industry actors. However, there were only 9 out of 365 micro, small, and medium enterprises (UMKM) in Batu, Bumiaji, and Junrejo that succeeded to enter into the export market. The primary challenges include limited capital, low product quality, and weak business management. Thus, there is a need for strengthened collaboration among stakeholders to enhance the local economic impact of the industry.